2008
DOI: 10.1080/13880200802215826
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Effect of Curcumin in Pure Versus in Extract Forms

Abstract: Curcumin isolated from turmeric (Curcuma longa L., Zingaberaceae) root was found to be anti-angiogenic in a human tissue-based angiogenesis assay. As a liposoluble compound, curcumin can be extracted from turmeric root with organic solvents such as ethanol or acetone. Curcumin in its pure form has poor solubility in water, potentially limiting its medicinal use for humans when it is taken orally or injected. This study attempted to investigate the possibility of improving curcumin's low solubility using an ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…1) is a natural compound found in the root of Curcuma longa L. (Zingiberaceae), which has been widely used as a yellow pigment, a spice in the food industry, and a traditional medicine in Asia. Mounting scientific evidence indicates that CUR is a versatile bioactive compound possessing antioxidant, 1 anti-inflammatory, 2 antihyperlipidemic, 3 liver antifibrotic, 4 antiangiogenic, 5 antineoplastic, and chemoprotective properties. 6 The diverse bioactivities displayed by this single natural compound have made CUR a subject of intense and broad investigations for potential functional and medicinal foods as well as drug development for the prevention and treatment of various diseases such as colon cancer, 7 cystic fibrosis, 8 inflammatory bowel disease, 9 and HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…1) is a natural compound found in the root of Curcuma longa L. (Zingiberaceae), which has been widely used as a yellow pigment, a spice in the food industry, and a traditional medicine in Asia. Mounting scientific evidence indicates that CUR is a versatile bioactive compound possessing antioxidant, 1 anti-inflammatory, 2 antihyperlipidemic, 3 liver antifibrotic, 4 antiangiogenic, 5 antineoplastic, and chemoprotective properties. 6 The diverse bioactivities displayed by this single natural compound have made CUR a subject of intense and broad investigations for potential functional and medicinal foods as well as drug development for the prevention and treatment of various diseases such as colon cancer, 7 cystic fibrosis, 8 inflammatory bowel disease, 9 and HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Curcuminoids are poorly soluble in water, but soluble in ethanol, methanol, acetone and DMSO (Li et al, 2011). The limit of curcumin solubility in water is 0.29% (w/w) (Liu et al, 2008).…”
Section: Effect Of the Turmeric Decoctum On Vegf And Ve-cadherin Exprmentioning
confidence: 99%
“…The optimum condition for good resolution was obtained with C18 column, methanolwater (50:50 v/v), at pH = 7, flow rate 1 mL/min and without any salts at room temperature. 1 Gradient technique by using methanol and water as mobile phase solvents 2 Isocratic method by using methanol and water as mobile phases with ratio of 50:50, respectively 3 Separation factor between BDMC and DMC 4 Resolution between BDMC and DMC 5 Resolution between C and DMC 6 Separation factor between C and DMC…”
Section: Optimization Of Analytical Hplc For Isolation Of Curcuminoidsmentioning
confidence: 99%
“…1). These compounds have many physiological properties, but lately, it was reported that curcumin is the main bioactive constituent of turmeric rhizome and has a wide range of pharmacological activities, including antiinflammatory [1,2], anticancer [1,3,4], anti-oxidant [1,5], anti-angiogenic [6], and immune modulatory [7]. Another study has also shown that cur-cumin is a potential chemotherapeutic agent for cancer as well as a promising agent in the treatment and prevention of Alzheimer's disease [8].…”
Section: Introductionmentioning
confidence: 99%